Flavonol‐mediated stabilization of PIN efflux complexes regulates polar auxin transport. (13th November 2020) - Teale, William D; Pasternak, Taras; Dal Bosco, Cristina; Dovzhenko, Alexander; Kratzat, Krystyna; Bildl, Wolfgang; Schwörer, Manuel; Falk, Thorsten; Ruperti, Benadetto; V Schaefer, Jonas; Shahriari, Mojgan; Pilgermayer, Lena; et al.
Abstract: The transport of auxin controls the rate, direction and localization of plant growth and development. The course of auxin transport is defined by the polar subcellular localization of the PIN proteins, a family of auxin efflux transporters. However, little is known about the composition and regulation of the PIN protein complex. Here, using blue‐native PAGE and quantitative mass spectrometry, we identify native PIN core transport units as homo‐ and heteromers assembled from PIN1, PIN2, PIN3, PIN4 and PIN7 subunits only. Furthermore, we show that endogenous flavonols stabilize PIN dimers to regulate auxin efflux in the same way as does the auxin transport inhibitor 1‐naphthylphthalamic acid (NPA). This inhibitory mechanism is counteracted both by the natural auxin indole‐3‐acetic acid and by phosphomimetic amino acids introduced into the PIN1 cytoplasmic domain. Our results lend mechanistic insights into an endogenous control mechanism which regulates PIN function and opens the way for a deeper understanding of the protein environment and regulation of the polar auxin transport complex. Synopsis: PIN‐FORMED (PIN) transporters regulate distribution of the phytohormone auxin in plant tissues. The current study shows that PIN core complexes are formed by PIN homo‐ and heterodimers, which are stabilized by the auxin transport inhibitor 1‐naphthylphthalamic acid (NPA) and natural flavonols. Quantitative mass spectrometry identifies PIN protein homo‐ and heterodimers at the plasma membrane, with PIN1 homodimers most prevalent NPA and naturally‐occurring flavonols stabilize PIN dimers Auxin treatment or PIN1 phosphomimetic amino acid substitutions reduce formation of PIN complexes Antibody‐mediated blocking of PIN1‐PIN1 interactions renders plants less sensitive to NPA Abstract : Identification of native PIN‐FORMED (PIN) auxin transporter complexes in Arabidopsis thaliana shows formation of dimers that are stabilized by the auxin transport inhibitor NPA and natural flavonols.